Soft power and its implications for political book cover designs (Al-Academy, 2024)
Art is one of the soft dimensions in exercising power and influencing the recipient, because it is a real mirror that reflects the culture of the country and the extent of its development. Art is a part of culture, which is one of the tools of soft power. Design is one of the parts of art, through which the designer can deliver a specific idea or message to the recipient and influence his thoughts and beliefs directly or indirectly, through design works that are employed with ideas that serve society and achieve goals. required. A country's reliance on its military power alone, regardless of its capabilities and modernity, represents a deduction from international support for it and support for its positions. Therefore, the major powers have historically not neglected to pay attention to the power of media, artistic and cultural discourse in an attempt to win international public opinion by reaching it and influencing it with the power of logic. . Hence, the researcher finds the following question: What is the role of the implications of soft power on the designs of political book covers?